2017
DOI: 10.1002/app.45948
|View full text |Cite
|
Sign up to set email alerts
|

Online prediction of the filtration performance of polypropylene melt blown nonwovens by blue‐colored glow

Abstract: In recently years, fine particulate matter (PM) pollution has drawn worldwide attention due to its serious threat to public health, visibility, climate, and ecosystems. The electret filter that can significantly improve the filtration efficiency without increasing the pressure drop has been widely used to for PM filtration. However, there were still some blind spots in the corona charging process, such as the interaction effects between the charging factors on the electret performances and the electric spark p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…Helical structures, which are found in many natural systems such as plant tendrils and fine wool, have been of great interest due to the unique spring‐like constructions, arousing the exploration of preparing biomimetic materials by researchers. It has been known that due to their excellent properties attributed to the small diameter of the fibers, micro/nanofibrous materials have found applications in broad areas in recent years . It is therefore expected that designing materials by coupling helical structures with micro/nanofibers may open a promising market in a broad range of areas.…”
Section: Introductionmentioning
confidence: 99%
“…Helical structures, which are found in many natural systems such as plant tendrils and fine wool, have been of great interest due to the unique spring‐like constructions, arousing the exploration of preparing biomimetic materials by researchers. It has been known that due to their excellent properties attributed to the small diameter of the fibers, micro/nanofibrous materials have found applications in broad areas in recent years . It is therefore expected that designing materials by coupling helical structures with micro/nanofibers may open a promising market in a broad range of areas.…”
Section: Introductionmentioning
confidence: 99%
“…These results imply that the aging resistance and long-term stability of the filtration efficiency were enhanced by the cyclic charging technology; the decay of the surface voltage further confirmed this inference ( Figure 8 e). We confirmed that the filtration efficiency would reach a stable value when the charging time exceeded the threshold value because the traps were saturated with the increase in charging time [ 29 ]. We set the charging time to 40 s and excluded the possibility that the improvement in the filtration efficiency was due to the indirect increase in charging time.…”
Section: Resultsmentioning
confidence: 54%
“…The corona charge process makes the charged ions deposited on the electret material to form surface charges [31] and trapped inside the material to form space charges [32,33]. The space charge in melt-blown PP electret air purification material mainly comes from the capture of interface traps [34].…”
Section: Relationship Between the Filtration Performance And The Heatmentioning
confidence: 99%